Architect work and interface with human health and life quality (Research, Society and Development, 2020)
The theoretical-philosophical, reflective, exploratory and qualitative study. Which aimed to reflect on the interfaces of the architect's work, health and quality of life of the human being. Architecture has not only evolved in terms of architectural planning to encompass greater solidity, utility and beauty of the built spaces / environments, but it has also grown in the face of the perception of the quality of those who will use the buildings. The human being with a good quality of life and, consequently, with health is able to fulfill himself in face of his needs and potential. It lacks opportunities for the exercise of well-being and healthy well-being and, for that, an interdisciplinary team is needed, among which, the professional architect, whose main scope of work consists of creating spaces / environments built in order to improve the quality of life of the people who live in them.